Virtual Tour as a Digital-based Guidance and Counseling Orientation Service in the Introduction of the School Environment - Amriana, Amriana; Fanan, M. Athoiful; Salsabila, Sayyida Aulia; Mardhiyah, Khairunnisa; Mumtaza, Muhammad Alif Mahdy (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2023)
This study aims to determine the role of virtual tour as a digital-based guidance and counseling orientation services in the introduction of the school environment. By understanding the potential that virtual tour technology has in the educational context, researchers hope that this can open up opportunities to provide more effective, informative, and in-depth orientation experiences for students. In this study, the researchers used the research method of literature review or literature study. Withall the data collected and researched comes from reading materials, or literature, as well as other relevant documentation materials, such as books, journals, papers, articles, and other materialsrelated to the subject of research. The results of this study are 1) Virtual tour allows students to explore school facilities firsthand, 2) in the virtual tour, information and introduction about school rules and important procedures can be included, and 3) Virtual tour can provide an introduction to educational programs, curriculum, to extracurricular activities available at school. In general, virtual tours play a big role in helping teachers, parents, and students in better understanding and identifying the school environment. This makes guidance and counseling (BK) orientation services more successful and can be a good source of information for all school personnel.